Matching services to markets : the role of the human sensorium in shaping service-intensive markets - Casanova, H. B. (Service systems and innovations in business and society collection., 2016)
Every creature builds its niche in engagement with its environment. Such engagements, repeated over time, invariably result in stable exchanges supporting a particular species. Every species maintains its exchanges using its unique sensorium, its own aggregated set of sensory channels it uses to see and frame the world around it. Our sensorium dictates the unique way we discover our worlds. It determines the reach, the range, the limits, the apprehended spectra, the blind spots, and the sutures among the sensory channels by which we gain inbound impressions of our wider environs. As well, our sensorium conditions how we think, judge, and how we launch outbound action, as we build our very human exchanges into societies. It engraves and projects itself on both the learnings and initiatives we deploy to impose meaning and intent onto our wider human world. It determines our structures, our processes and the materiel we use to build out our socially networked exchanges. In the economic realm, these exchanges, structured uniquely by our very human sensorium, become formalized as Markets. Understanding our sensorium, seeing its projective power, its emergent properties, and its corresponding fault lines and tectonic zones as it governs and even dictates our social structures, can greatly clarify our understanding of market architecture itself: structure, process, and materiel. With these deep landmarks mapped out, we can catalyze great progress in further consolidating a robust Science of Service and Service Innovation. Spurring that on is the dominant intent and exploration of this book.